Aktivitas Antioksidan dan Kadar Kafein Kombucha Kopi [Antioxidant Activity and Caffeine Content of Coffee Kombucha] - Parhusip, Adolf J.N. (FaST - Jurnal Sains dan Teknologi (Journal of Science and Technology), 2022)
Kombucha is the result of the fermentation of tea and sugar by a kombucha culture starter known as SCOBY (Symbiosis Culture of Bacteria and Yeast). One of the efforts that possible to improve the functional aspects of coffee is by the fermentation process of kombucha. Based on that hypothesis, the goal of this research is to develop the potential of coffee through kombucha fermentation. This research involves two stages that include stage I research with type of coffee (arabica, robusta, liberica) and fermentation time (0, 3, 6, 9 days) as the factors, and stage II research performed on coffee kombucha with selected types of coffee. In stage I research, analysis of antioxidant activity was performed to determine the treatment that produced coffee kombucha with the highest antioxidant activity, supported by analysis of total lactic acid bacteria, total yeast, and pH value. In stage II research, analysis of caffeine content was performed to determine the best fermentation time that produces coffee kombucha with the highest caffeine content. Another supporting analysis carried out in this research is water content analysis of coffee grounds and the identification of microbes in the liquid kombucha starter. The treatment that can produce coffee kombucha with the highest antioxidant activity is arabica coffee with an average IC50 value of 4689,41 ppm and 9 days of fermentation with an average IC50 value of 4988,90 ppm. Analysis of caffeine content carried out on arabica coffee kombucha showed an increment in caffeine content during the fermentation process, as the highest caffeine content is 0,77% on the 9th day of fermentation. BAHASA INDONESIA ABSTRACT:Kombucha merupakan hasil fermentasi teh dan gula oleh starter kultur kombucha yang disebut sebagai SCOBY (Symbiosis Culture of Bacteria and Yeast). Salah satu upaya yang dapat dilakukan untuk meningkatkan aspek fungsional kopi adalah dengan proses fermentasi kombucha. Berdasarkan hipotesis tersebut penelitian ini dilaksanakan guna mengembangkan potensi kopi lewat fermentasi kombucha. Penelitian ini terbagi menjadi 2 tahap yang meliputi penelitian tahap I dengan faktor jenis kopi (arabika, robusta, liberika) dan lama fermentasi (0, 3, 6, 9 hari) serta penelitian tahap II yang dilakukan pada kombucha kopi dengan jenis kopi terpilih. Analisis aktivitas antioksidan dilakukan pada tahap I untuk menentukan perlakuan yang menghasilkan kombucha kopi dengan aktivitas antioksidan tertinggi, didukung dengan analisis total bakteri asam laktat, total khamir, dan nilai pH. Pada tahap II, dilakukan analisis kadar kafein untuk menentukan lama fermentasi terbaik yang menghasilkan kombucha kopi dengan kadar kafein tertinggi. Analisis pendukung lain yang dilakukan adalah analisis kadar air bubuk kopi dan identifikasi mikroba pada starter kombucha cair. Perlakuan yang dapat menghasilkan kombucha kopi dengan aktivitas antioksidan tertinggi adalah jenis kopi arabika dengan nilai IC50 rata-rata sebesar 4689,41 ppm dan lama fermentasi 9 hari dengan nilai IC50 rata-rata sebesar 4988,90 ppm. Analisis kadar kafein dilakukan pada kombucha kopi arabika menunjukkan terjadinya peningkatan kadar kafein selama proses fermentasi dengan kadar tertinggi pada fermentasi hari ke-9 yaitu 0,77%.